Representation of an Asian-Australian Gay in Hsu-Ming Teoâ€™s Behind the Moon - Astuti, Amelberga Vita N.P. (FISIP Universitas Atma Jaya Yogyakarta, 2018)
This paper examines how a novel Behind the Moon (2005) provides literary representations of an Asian migrantâ€™s transforming sexual identities in Australia. Applying Morrisâ€™s concept of a â€œpolitics of surveillance,â€ it argues that approaches of strict control leads to an initial clash of cultures, and ultimately either to mutual transformation or a reinforcement of lack of agency/sexual difference. The analysis shows that the novel displays aspects of the cultural complexities of sexual identity formation regarding the characterâ€™s identity as an Asian homosexual in Australia. As to transformation setting, the city is a spatial metaphor for cultural confinement and surveillance.